PEMBUATAN PROGRAM APLIKASI PENJUALAN 378 JAKARTA - Juniarto Salim; Desi Arisandi; Jap Tji Beng (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Information technology is a set of tools that assist work related to informations and informations processing. The sales processes at 378 Jakarta actually have applied information technology and social medias, however the recordings of products and customer’s informations were still manually recorded.The manual processes often cause errors when searching products and listing customers who are ordering. Therefore, a database using MySQL and PHP was made to support the application program. SDLC methods can to support sales processes, sales reports making, and other processes in 378 Jakarta. The functions of the application is to support products sales transasction and to generate some reports (such as sales report, best sellers report, and transaction report). The application has been tested by using blackbox testing. The test results were detected while operating the application, unfortunately there is an additional program added charges. The additional program has been successfully added, tested, and considered able to operate without any specific problem found.